Creative thinking among today's Muslims: barriers and breakthroughs - Badi, Jamal Ahmed Bashier ((معهد إسلام المعرفة (إمام) بجامعة الجزيرة (السودان), 2007)
Creative thinking and problem solving is of extreme concerns in the Western research for the last half century. The findings of these researches are being implemented and applied in all walks of life: education, administration, leadership, etc. Not only that, it is used in political mobilization, advertisement, propaganda, mind-leading, influencing attitudes through perceptual manipulation and even as a powerful tool to promote Globalization throughout the whole World.